2022
DOI: 10.3390/su15010296
|View full text |Cite
|
Sign up to set email alerts
|

Robust Wavelet Transform Neural-Network-Based Short-Term Load Forecasting for Power Distribution Networks

Abstract: A precise short-term load-forecasting model is vital for energy companies to create accurate supply plans to reduce carbon dioxide production, causing our lives to be more environmentally friendly. A variety of high-voltage-level load-forecasting approaches, such as linear regression (LR), autoregressive integrated moving average (ARIMA), and artificial neural network (ANN) models, have been proposed in recent decades. However, unlike load forecasting in high-voltage transmission systems, load forecasting at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…They trained a multi-headed temporal convolutional network using historical load, calendar variables, and weather variables to forecast 1-step, 5-steps, and 10-steps future load values. In [27], the author proposed a hybrid STLF model for volatile and non-stationary distribution networks using a robust wavelet transformation and neural network. Their simulation show better results when compared with traditional forecasting models.…”
Section: Related Workmentioning
confidence: 99%
“…They trained a multi-headed temporal convolutional network using historical load, calendar variables, and weather variables to forecast 1-step, 5-steps, and 10-steps future load values. In [27], the author proposed a hybrid STLF model for volatile and non-stationary distribution networks using a robust wavelet transformation and neural network. Their simulation show better results when compared with traditional forecasting models.…”
Section: Related Workmentioning
confidence: 99%
“…Although the first-generation methods were successful in the past, researchers continue to utilize them for feature extraction purposes [17,18]. In recent years, ANN-based models have been widely adopted, primarily due to their proficiency in processing nonlinear data.…”
Section: Introductionmentioning
confidence: 99%
“…The dataset comprises two years of hourly demand data for a city region, considering various features such as temperature, humidity, and holidays. Wang et al in [17] suggested using variational mode decomposition (VMD), empirical mode decomposition (EMD), and empirical wavelet transform (EWT) to convert time-domain demand data into the frequency domain. The processed data are then passed to a Bi-LSTM layer before signal reconstruction at the output.…”
Section: Introductionmentioning
confidence: 99%
“…Their models, VMD-CNN-long short-term memory (LSTM) and VMD-CNN-gated recurrent unit (GRU), showcased versatility, adeptly managing seasonal and daily energy consumption variations. Wang et al [27], in their recent endeavors, proposed a wavelet transform neural network that uniquely integrates time and frequency-domain information for load forecasting. Their model leveraged three cutting-edge wavelet transform techniques, encompassing VMD, empirical mode decomposition (EMD), and empirical wavelet transform (EWT), presenting a comprehensive approach to forecasting.…”
Section: Introductionmentioning
confidence: 99%